An Academic Exploration: Investigating Phytodiversity Research in Sanjay- Dubri Tiger Reserve, Sidhi, Madhya Pradesh: Exploring Phytodiversity Research in an Ecologically Important Tiger Reserve (Journal of Advances and Scholarly Researches in Allied Education, 2023)
The Sanjay –Dubri Tiger reserve, located in the Sidhi district of the Madhya Pradesh, India, is awell-preserved ecological area known for its diverse range of species. This review article undertakes anacademic exploration to examine and consolidate the substantial body of research on Phytodiversityconducted within the ecologically important reserve. The main aim of this review is to present athorough examination of the research endeavours focused on the gaining a comprehensiveunderstanding of the varied plant life present within the Sanjay–Dubri Tiger Reserve Sidhi . Search wasconducted on databases by using related keywords. Further, Analysis of the results is done to findresearch done specifically to Sanjay-Dubri Tiger Reserve, Sidhi district of Madhya Pradesh. The analysisand findings reveal that Limited research is conducted on phytodiversity of Sidhi district and most ofthem are old studies. In particularly Sanjay-Dubri Tiger Reserve, only 4 researches were found whichindicate that this region is not hot region for researchers. We suggest researchers to conductphytodiversity studies, regeneration and research related to distribution pattern of the flora in this regionbecause of its diverse range of species. In conclusion, this article provides valuable resources foracademics, researchers and policymakers who have interest in the dynamic filed of biodiversity researchwithin the distinctive context of the Sanjay-Dubri Tiger Reserve in Sidhi, Madhya Pradesh.